Physiological profile of Australian elite female basketball players according to playing position. - Legg, J. S.; Williams, K. J.; Pyne, D. B.; Semple, S. J.; Ball, N. (Journal of Australian Strength and Conditioning, 2017)
The aim of this study was to investigate physiological and anthropometric characteristics in elite female basketball players according to playing position as previous research has focused on males and junior players. Twenty-Six Australian female representative basketball players (24.1 ± 3.6 y; mean ± SD) participated in this cross-sectional study. According to positional roles, players were categorized as guards (n=9), forwards (n=5) and centres (n=11). The tests included anthropometric assessment of skinfolds (mm) 78.65 ± 16.05, height (m) 181.88 ± 8.98 and mass (kg) 73.45 ± 8.14, a 20m sprint test (s) 3.39 ± 0.18, and the Yo-Yo intermittent Recovery Level 1 test (level) 17.26 ± 1.04. Countermovement jump (CMJ) data was collected via a Gymaware™ optical encoder and drop jump testing data was collected via a Swift Speed Mat. Physiological differences were evident between the positional playing groups with centres producing significantly greater peak force (N) 2641 ± 864 than guards 2113 ± 134 (p<0.05). Centres were substantially heavier and taller than guards with mean differences of 11 kg and 17 cm respectively. The overall differences in physiological measures between the playing groups was limited suggesting that skills in female Australian basketball players play a larger role in determining international success once baseline performance markers have been achieved.